Knowledge Society and Lifelong Learning - Rekun, Ivan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
During times of high unemployment and a lack of job security, further vocational training is all too often put on the sidelines in favors of economic competition objectives and labour market flexibility. Most people change careers several times in their lives, even though what they learned in school was designed to prepare them for their first career; the pace of change is so fast that technologies and skills to use them become obsolete. School-to-work transition is insufficiently supported. We cannot prepare people to live in a twenty-first century world using nineteenth century technology.

W czasach recesji wysokie globalne bezrobocie coraz bardziej marginalizuje cele gospodarcze, konkurencję i elastyczność rynku pracy. Większość ludzi narzeka na swoje życie i pracę, ponieważ są zmuszeni zmieniać pracę kilka razy w ciągu swojego życia, mimo wiedzy i umiejętności, które otrzymali w szkole. Tempo zmian jest tak duże, że technologia i wiedza szybko ulegają deprecjacji. Szkolnictwo nie nadąża za zmianami w stechnicyzowanym społeczeństwie. Nie można przygotować ludzi do życia w XXI wieku wykorzystując technologię z XIX wieku.